The effects of 5-HT on vascular endothelial dysfunction in patients with panic disorder - Yueqi Feng; Xixi Li; Zijia Li; Xinyi He; Yanqing Tang; Wen Tian (Frontiers in Cardiovascular Medicine)
Panic Disorder (PD) is a prevalent psychiatric condition characterized by recurrent episodes of acute severe anxiety. These episodes frequently present with symptoms that overlap with those of cardiovascular diseases (CVD), such as elevated blood pressure and chest pain. Despite the prevalence and impact of this comorbidity, the underlying mechanisms are not well understood and remain underexplored. This review synthesizes current understanding and recent findings on the role of 5-hydroxytryptamine (5-HT) in the intersection of PD and vascular dysfunction. 5-HT, a critical inhibitory neurotransmitter, has been implicated in the etiology of PD and linked to panic symptoms. This review underscores the importance of 5-HT in modulating vascular tone through its action on 5-HT1B and 5-HT2A receptors, influencing the production of nitric oxide (NO) and the subsequent vasomotor response. Furthermore, the impact of 5-HT system on platelet activation and aggregation adds another layer to the complex relationship between PD and CVD. Selective serotonin reuptake inhibitors (SSRIs) have shown promise in improving vascular endothelial function. However, the influence of SSRIs on CVD outcomes remains a controversial issue with conflicting findings from various studies. The review also highlights the role of the PI3K/Akt/eNOS signaling pathway in 5-HT's influence on vascular endothelial function. In conclusion, the intricate relationship between PD, 5-HT, and vascular endothelial function warrants further investigation. A deeper understanding of these mechanisms could lead to more effective treatments for PD and related CVD, ultimately improving patients’ mental health and cardiovascular outcomes.